An assessment of the manufacturing capabilities of Nigerian funiture makers: case study of Lagos, Nigeria (2011)
This study examines the manufacturing capabilities of the Nigerian furniture industry. An extensive review of literature was carried on wood; structure, seasoning types, properties and finishing. Also, a review on wood furniture manufacturing processes, in terms of tools, equipment, design, ergonomics, finishing was carried out. Interview, observation, discussion and survey method were used for data gathering from some selected furniture workshops in Lagos. An assessment of the furniture industry in Nigeria in terms of processes, finishing techniques, aesthetics, tools and equipment, was carried out and compared with standards furniture manufacturing industry in Nigeria in terms of processes from literature and practices obtained in some developed countries. The study concludes that improvement and investment in the areas of equipment, machines, improvement in power supply and a programme to train the local furniture makers are required to improve the output from the sector.